FACTORS AFFECTING THE DISCLOSURE OF SUSTAINABILITY REPORTS OF TRANSPORTATION COMPANIES IN INDONESIA - Nawang Kalbuana; Muhamad Taqi; Lia Uzliawati; Dadan Ramdhani; Munawar Muchlish (International Journal of Economics, Business and Accounting Research (IJEBAR), 2023)
This study was made with the aim of testing the influence of variables of company age, company size, and CEO narcissism on sustainability reports where the sample from this study is transportation sector companies listed on the Indonesia Stock Exchange (IDX) for the 2017-2021 period. The data used is financial statement data and visits the websites of each company. The technique in selection of samples was carried out using the purposive sampling method and obtained by 12 companies with a research period of 2017-2021. The data analysis method that the authors used in this study was multiple linear regression analysis. The study results show that simultaneously the variables of company age, company size, and CEO narcissism have a significant effect on sustainability reports. Partially, the age of the company has no significant effect on the sustainability report, while the size of the company and the narcissism of the CEO have a positive and significant effect on the sustainability report.